PROTECTION OF OIL REFINERY EQUIPMENT FROM CORROSION CAUSED BY LIGHT PETROLEUM PRODUCTS OBTAINED FROM UKRAINIAN OIL FIELDS - ROMANCHUK, OLEKSANDR; TOPILNYTSKYY, PETRO (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The application of corrosion inhibitors remains one of the most efficient approaches to safeguarding oil refining equipment from degradation. In the context of modern ecological and economic demands placed on industrial technologies, inhibitors synthesized from renewable natural resources are gaining increasing importance. This study aimed to analyze the corrosion behavior of refinery equipment exposed to straight-run gasolines derived from Ukrainian oil fields and to assess the protective performance of newly synthesized organic inhibitors in such environments. The inhibitors under investigation were produced on the basis of higher distilled fatty acids (HDFA) obtained from natural animal fats and further modified using diethanolamine (DEA) and diaminoethane (DAE). The reaction between HDFA and ethylenediamine resulted in the formation of mono- and disubstituted ethylamides (MZEA and DZEA), while the interaction of HDFA with diethanolamine produced dihydroxyethylamides of higher fatty acids (DHEA). The protective efficiency of these inhibitors was assessed via the gravimetric method, which determines the mass loss of metal samples immersed in a medium both with and without the inhibitor. Experimental studies were performed in environments consisting of straight-run gasolines obtained from the Kachanivska, Novohryhorivska, and Bugruvativska fields, as well as a blend from the Yablunivske field (Ukraine). Each gasoline sample was mixed with an aqueous saline solution in a 9:1 ratio. The analysis demonstrated that the efficiency of the inhibitors is strongly influenced by both the composition of the gasoline and the chemical nature of the inhibiting agent. The highest degree of protection—up to 95.45%—was recorded for the DHEA inhibitor in gasoline derived from Kachanivska oil. Consequently, the corrosion inhibition efficiency is determined not only by the molecular characteristics of the inhibitor but also by the physicochemical properties of the fuel medium. These inhibitors exhibit optimal performance in low-acid, low-sulfur, and light gasoline environments, while in more aggressive conditions their protective capacity decreases due to complex adsorption behavior and partial destruction of the formed protective layer by active components of the fuel.